A Comparative Study of SOC Estimation Based on Equivalent Circuit Models - He, Jiangtao; Meng, Shujuan; Yan, Fengjun (Frontiers in Energy Research, 2022)
This article presents a comparative study of the state of charge (SOC) estimation using Kalman filter (KF)-based estimators and H-infinity filter. The aim of this research is to obtain the optimal estimator by evaluating the SOC accuracy, robustness, and computation time under varying current noise assumptions. In the KF-based estimators, the extended Kalman filter (EKF), unscented Kalman filter (UKF), and cubature Kalman filter (CKF) are mostly used in the SOC estimation area. The mixed driving cycle profiles are used to test the battery to simulate the complex driving conditions in real electric vehicles (EVs). Also, white noise and bias noise are added into the current data to imitate the inaccurate sensors in EVs. The normal equivalent circuit models (ECMs) and augmented ECMs with varying RC branches are thoroughly compared to acquire the best estimator under varying situations.